A cross-sectional study of predictive factors of health literacy among rheumatoid arthritis patients in China - Liu, Ting; Meng, Weifen; Wang, Wenlong; Sun, Guomin; Chen, Xi; Lu, Yan; Qin, Weiping; Wang, Yan; Zhang, Lu; Zheng, SuHua (Frontiers in Psychology, 2024)
Objective To investigate the factors that influence health literacy (HL) among Chinese patients with rheumatoid arthritis (RA) and furnish theoretical underpinnings for the development of intervention strategies aimed at enhancing patients’ quality of life. Methods From May 2022 to December 2022, a comprehensive survey was conducted among both outpatients and inpatients diagnosed with (RA) in a tertiary hospital in China. The survey utilized various instruments, including a general information questionnaire, a chronic disease patient health literacy scale, the Health Assessment Questionnaire-Disability Index (HAQ-DI), the Chinese-translated Rheumatoid Arthritis Self-Efficacy Scale, the Chinese-translated Rheumatoid Arthritis Stigma Scale, and the Chinese-translated Compliance Questionnaire for Rheumatology Treatments. Results The average scores of HL, self-efficacy, medication adherence, and disability index were 83.54 ± 17.43, 84.91 ± 14.37, 70.16 ± 11.24, and 0.26 ± 0.44, respectively. HL in Chinese RA patients was negatively correlated with age, erythrocyte sedimentation rate (ESR), number of tender joints, number of swollen joints, and disease activity, while positively correlated with self-efficacy and medication adherence. Age, disease activity, disability index, self-efficacy, and medication adherence are predictive factors of HL, and a predictive model has been initially constructed. Conclusion In the management of RA, healthcare professionals should develop and implement effective intervention measures by focusing on improving medication adherence, enhancing patients’ self-efficacy, improving patients’ physical function, and reducing disease activity. This will help enhance the health literacy and promote clinical outcomes in RA patients.